FORMATION OF ELEMENTS OF A SCIENTIFIC WORLDVIEW AMONG PRIMARY SCHOOL CHILDREN (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The formation of elements of a scientific worldview among primary school children is an important stage in the educational process. The article examines the main approaches and methods aimed at developing cognitive activity, critical thinking, and research skills in children of primary school age. Special attention is paid to the role of the teacher and the learning environment in shaping a holistic perception of the surrounding world based on scientific knowledge. The article describes methods for integrating subject-specific knowledge and developing children's ability to draw independent conclusions and approach the world with awareness.